Calvyn en die eenheid van die kerk - Coetzee, C. F. C. (Faculty of Theology, University of the Free State, 2006)
The subject of church unity remains one of the most relevant and most important subjects that Reformed churches have to deal with. We believe the one, holy, catholic and apostolic church. But we also experience the tragic disunity of the church. Church unity therefore is not only a gift but also a calling. From a reformed perspective it is always important to take note of the viewpoint of John Calvin. He was called a “champion of church unity” (Wendel). For Calvin, the primacy of the Word of God and therefore the emphasis on the truth of the doctrine was not negotiable. But he distinguished between fundamental and mediocre matters. He was also willing to accept differences in liturgy and church order provided that there was unity in doctrine. The viewpoint of Calvin can definitely benefit the striving for unity amongst the different Reformed church communities in South Africa.
Keywords: Church unity; Calvin; Truth; Disunity